MORPHOLOGICAL VARIABILITY OF PREMOLARS ROOTS - Maria-Antonela Beldiman; Elena Luca; Cristina Iordache; Anca Mihaela Vițalariu; Liana Aminov (Romanian Dental Association for Education, 2020)
Aim of the study The successful endodontic therapy is due to the knowledge of the root and canal morphological variability of premolars. The aim of this study is to present this variability of number of roots/canals for the first and second premolars, both upper and lower, and to compare the results with data from literature. Material and methods Our study was done on a group of 52 teeth (28 upper premolars and 24 lower premolars) selected respecting some criteria, and were extracted for orthodontic purposes. Results Regarding the root morphology, the study showed that, for the first maxillary premolars, were registered 12 premolars with 2 roots (75%), 3 had a single root, and a single first maxillary premolar, 3 roots. The second maxillary premolars showed less variability: thus, the premolars with 2 roots were 9 in number, while only 3 second premolars were found with a single root. The root and canal morphology of the upper premolars in our studied group revealed a morphological pattern already mentioned in the literature. Conclusions The root morphology, especially the endodontic configuration of the root structure can be a decisive aspect in treating and maintaining a tooth on the dental arch, and use it for a prosthetic restoration.